The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1468-3083.2008.02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of some treatment modalities of rosacea

Abstract: Azelaic acid 20% cream provides an effective and safe alternative to metronidazole 0.75% cream or permethrin 5% cream with the added benefit of increased patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Most of the other comparisons consisted of single studies and investigated drug, e.g. permethrin, benzoyl peroxide, benzoyl peroxide combined with clindamycin, sodium sulphacetamide 10%/sulphur 5%, pimecrolimus, topical erythromycin, topical ciclosporin, ethoxybenzylaldehyde and adjunctive benefit of a polyhydroxy acid (PHA) regimen and flavonoid‐rich cream 15,16,28,39–49 . The results are reported in Table 3, but are not discussed as most of these studies were judged to be at high risk of bias and had skewed or unusable data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the other comparisons consisted of single studies and investigated drug, e.g. permethrin, benzoyl peroxide, benzoyl peroxide combined with clindamycin, sodium sulphacetamide 10%/sulphur 5%, pimecrolimus, topical erythromycin, topical ciclosporin, ethoxybenzylaldehyde and adjunctive benefit of a polyhydroxy acid (PHA) regimen and flavonoid‐rich cream 15,16,28,39–49 . The results are reported in Table 3, but are not discussed as most of these studies were judged to be at high risk of bias and had skewed or unusable data.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence for the effectiveness of permethrin was inconclusive and therefore further trials with a rigorous study design are required 28,45 …”
Section: Discussionmentioning
confidence: 99%
“…All medications and cosmetics were discontinued from at least 2 weeks prior to participation to the end of the treatment course . Identical oil‐free moisturizing creams, oil‐free sunscreen creams, and gentle soap‐free cleansing bars were prescribed for all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the possible role of Demodex folliculorum in the pathophysiology of rosacea, scabicidal agents such as crotamiton, lindane and permethrin could be effective options against this condition. Only two randomized controlled clinical trials have studied the benefits of permethrin 5% cream on signs and symptoms of rosacea patients; nevertheless, none assessed its effects on Dd . Two other clinical trials have studied the acaricidal effects of permethrin on Dd in various Demodex ‐related dermatological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter observational uncontrolled study of 2456 patients (aged 2–70 years), reported that use of Mimyx was associated with clinical improvement (including pruritus, erythema, excoriation, dryness, lichenification, scaling, and sleep quality) and reduction of topical steroid usage 61. EpiCeram is triple-lipid barrier repair cream containing ceramides, cholesterol, and free fatty acids.…”
Section: Therapy Of Atopic Dermatitis: Overviewmentioning
confidence: 99%